Multifaceted exploration of Boerhaavia diffusa Linn : Antifungal, Antimicrobial, Antioxidant and Phytochemical insights - Dr. Remeshkumar. S; Dr.Jayalekshmi.R; Dr.Biju.C (Revista Electronica de Veterinaria, 2025)
Boerhaavia diffusa Linn. (Thazhuthama) is a medicinal plant that has been used for centuries in traditional medicine across India, Africa, and other regions. Known for its diuretic, anti-inflammatory, liver-protective, and antimicrobial effects, Boerhaavia diffusa holds significant potential as a therapeutic agent in modern pharmacology. This study explores the Antifungal, Antimicrobial, Antioxidant and phytochemical properties of Boerhaavia diffusa, providing an in-depth look at its bioactive compounds and their therapeutic applications. Recent scientific research has confirmed many of the plant’s traditional uses, and advanced studies have revealed a variety of compounds responsible for its pharmacological effects. Among the most notable bioactive constituents are alkaloids, flavonoids, phenolic acids, steroids, and glycosides, all of which contribute to its efficacy in treating infections, oxidative stress-related diseases, and inflammation. This study consolidates the latest findings on the plant’s medicinal properties and highlights its potential as a natural alternative to synthetic pharmaceutical agents, with a focus on its Antimicrobial, Antioxidant, Antifungal activities and Phytochemical properties.